Development of ribbon ion beam source and transport system for industrial applications - Masunov, E.S.; Polozov, S.M.; Kulevoy, T.V.; Kuibeda, R.P.; Pershin, V.I.; Petrenko, S.V.; Seleznev, D.N.; Shamailov, I.M.; Sitnikov, A.L. (Вопросы атомной науки и техники, 2008)
The design of ribbon ion source and transport system is discussed in this paper. This system is created at ITEP for ion beam implantation in semiconductor technology. The Bernas type ion sources are used for ribbon ion beam production. The periodic system of electrostatic lenses is proposed for intensive ion beam transport. The results of implanter component development are observing. Розглядаються питання, пов'язані з розробкою стрічкового іонного пучка і системи транспортування. Система імплантації розробляється в ІТЕФ для імплантації іонного пучку у напівпровідники. Для одержання стрічкового іонного пучка використається джерело типу "Бернас". Для транспортування пучку запропоновано використати періодичну систему електростатичних лінз. Розглядаються результати розробки окремих частин імплантору. Рассматриваются вопросы, связанные с разработкой ленточного ионного пучка и системы транспортировки. Система имплантации разрабатывается в ИТЭФ для имплантации ионного пучка в полупроводники. Для получения ленточного ионного пучка используется источник типа «Бернас». Для транспортировки пучка предложено использовать периодическую систему электростатических линз. Рассматриваются результаты разработки отдельных частей имплантора.